Tailoring precipitation behavior of carbonitrides in high manganese-aluminum steels via microalloying elements - Erkang Liu; Wentao Wu; Youliang Zhao; Xin Tan; Shuxu Nie; Qingzhi Yan; Min Xia; Hongyan Guo; Manchao He; Changchun Ge (Journal of Materials Research and Technology)
The growing demand for lightweight materials to enhance fuel efficiency and reduce carbon emissions has intensified research into high manganese-aluminum steels, which combine exceptional ductility, reduced density, and cost efficiency. This study examines how microalloying elements (titanium, rare earth, and nickel) modify the precipitation behavior of carbonitrides in these steels. Through FESEM/EDS characterization and thermodynamic simulations using FactSage 8.1, we demonstrate that microalloying additions diversify carbonitride phases from initial AlN, Mn(S,Se)–AlN, and Al2O3–Mn(S,Se)–AlN formations into six distinct types, including Ti(C,N) and its composite variants. Specifically, microalloying lowers solidus/liquidus temperatures, enabling more uniform nucleation and finer precipitate formation. Titanium preferentially combines with carbon and nitrogen, replacing detrimental AlN inclusions with refined Ti(C,N) particles. Rare earth elements optimize carbonitride size and distribution by controlling elemental diffusion during solidification, while nickel mitigates titanium segregation to enhance nucleation uniformity. These insights establish practical strategies for tailoring carbonitride precipitation in industrial manufacturing processes, effectively connecting fundamental research with the production of high-performance, high-manganese-aluminum steels.